Low irradiance pulses improve postharvest quality of spinach leaves (Spinacia oleraceae L. cv Bison). - Gergoff Grozeff, Gustavo Esteban (2013)
The aim of this work is to extend and improve the postharvest life of mature spinach leaves using clean technologies like the use of short pulses of light at low irradiance. After harvest spinach leaves were immediately sealed in polyethylene bags in the laboratory. These bags were placed in a dark chamber at 23 ◦C under continuous dark or with the application of light pulses (LP) consisting of 15 min each 2–6 h or 7 min each 2 h for 3 d. The chosen irradiance, 30 mol m−2 s−1 PPFD, corresponded to the light compensation point previously measured in spinach plants under greenhouse conditions. After the leaves were treated with LP for 3 d, all the samples were transferred to a chamber at 4 ◦C under continuous dark for another week. Senescence was triggered in leaves under continuous dark after 3 d of storage and delayed in those receiving LP. In addition ascorbic acid and glutathione contents were kept higher in LP-treated than in untreated spinach. These trends were conserved after storage under continuous dark and refrigeration for another week. When LP was applied in combination with 1-MCP the antioxidant capacity was further improved. These results demonstrate that short LP of low irradiance can be used to extend and to improve postharvest life of mature spinach leaves.